FUNGSI PUPULAN CERPEN LUH JALIR - Saputra, I Made Dwi (Humanis, 2014)
This research examines the short story pupulan Jalir Luh Mas Ruscitadewi Sagung AA works. In the short story, there are nine short stories, and sources of data in this study there are five stories that Jalir Luh, Magalung, Purusa, Tepen Bulan and Buung. This research using the theory of functions. Methods and techniques in the study were divided into three stages, namely stages refer to the provision of data using methods supported by technical translation and recording techniques. Stage of data analysis using descriptive qualitative analytic techniques. Stage presentation of results of data analysis using informal methods supported by deductive and inductive techniques. The Functions contained in the short story Jalir Luh, Magalung, Purusa, Tepen Bulan and Buung include religious functions which can be used as a guide to behave. The function of education to discuss the moral education contained in the household and socially. Social functions that loyalty has a function to teach us to always be faithful to your partner and female functions can now also holds the status as purusa is always synonymous with men.
Keywords: short story, Luh Jalir, function.